Understanding the significance variables for fabrication of fish gelatin nanoparticles by Plackett-Burman design - Subara, Deni; Jaswir, Irwandi; Al-Khatib, Ma'an Fahmi Rashid; Noorbatcha, Ibrahim Ali (IOP Publishing, 2017)
The aim of this experiment is to screen and to understand the process variables on the fabrication of fish gelatin nanoparticles by using quality-design approach. The most influencing process variables were screened by using Plackett-Burman design. Mean particles size, size distribution, and zeta potential were found in the range 240±9.76 nm, 0.3, and −9 mV, respectively. Statistical results explained that concentration of acetone, pH of solution during precipitation step and volume of cross linker had a most significant effect on particles size of fish gelatin nanoparticles. It was found that, time and chemical consuming is lower than previous research. This study revealed the potential of quality-by design in understanding the effects of process variables on the fish gelatin nanoparticles production.